Ecological knowledge and sustainable planning in Nigeria: a reflection on the Yorubas of South-Western Nigeria - Ibrahim, Oladayo Ramon (Human Geography Journal, 2017)
In pre-colonial times, African people survived by acquiring and preserving community knowledge of the environment and the relationships between human and non-human elements. The paper is based primarily on secondary data, and examines the relationships between African people, especially Yoruba people of southwestern Nigeria and the land and how understanding this relationship can help our quest for a more effective and sustainable regional planning. The study   investigates the indigenous Yoruba Ecological Thoughts and Beliefs and how these affected the ways people have interacted with the environment. The result shows that there is a lot that modern planning can gain from the culture-environmental relationships of the indigenous people.Indigenous knowledge is the cornerstone of several convergent trends in social science thinking and development administration practice. With the failure of grand theories of development, social sciences focus on middle-range theories that are site – and time-specific (indigenous knowledge). Both traditional knowledge and modern science and technology should be complementary in the development process and should be properly integrated. People are the subject of development.   Development is supposed to suit the people and not the people to suit development. If Africa does not learn this lesson now, all our efforts at the development will be in vain, because Africa is ultimately only as strong as its communities are.